The influence of concurrent cognitive tasks on motor performance in people with traumatic brain injury: a pilot study. (3rd October 2022) - Jung, Taeyou; Katase, Ai; Wagatsuma, Mayumi; Fujii, Takuto; Jung, Youngok; Jeng, Brenda; Chaparro, Gioella
ABSTRACT: Background: Performing dual-tasks is often required for completing activities of daily living. Limited research investigated the effects of dual-tasking on gait in people with Traumatic Brain Injury (TBI). Purpose: To investigate the effects of cognitive tasks on gait in people with TBI Methods: Seven individuals with TBI and nine controls completed walking under three conditions; usual walking, walking with questions and answers, and walking with word generation while 3D motion analysis system captured gait. Results: Significant group x condition interactions were found in which TBI group showed greater changes in speed ( p < .01), cadence ( p = .07), and ankle kinematics ( p = .03) as cognitive task became more complex from usual walking to walking with word generation. TBI group decreased speed ( p = .02), stride length ( p = .01), and hip kinematics ( p = .03) as concurrent task became more complex. The control showed decreases in speed ( p = .01), stride length ( p = .01), and joint kinematics in the hip ( p = .03) and knee ( p = .01) as the complexity of concurrent cognitive task increased. Conclusion: People with TBI have greater difficulty walking with a cognitive task and show greater compromises in gait performance as the task complexity increases when compared to those without TBI. Clinicians should consider the use of progression in cognitive tasks for dual-task gait training.